Role of Virtual/ Digital Libraries in E-Learning - Hiremath, Suvarna S.; Lalasangi, Somashekar; Acharya, Shivakumar (Current Approaches in Science and Technology Research Vol. 14, 2021)
Today the concept of e-learning or online learning is getting emphasis in many Organizations like academic, research, corporate or government. But method of implementation of e-learning is still a question. Many Organizations have developed separate IT based systems for e-learning. Digital Library provides a and compatible base for e-learning module. This article deals with various aspects of e-learning, Strategies for e-learning implementation, role of digital libraries in developing e-learning.